2018
DOI: 10.1186/s12883-018-1036-1
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and Design of a Statewide Cohort to examine efficient resource utilization for patients with Intracerebral hemorrhage (EnRICH)

Abstract: BackgroundIntracerebral hemorrhage is a devastating disease with no specific treatment modalities. A significant proportion of patients with intracerebral hemorrhage are transferred to large stroke treatment centers, such as Comprehensive Stroke Centers, because of perceived need for higher level of care. However, evidence of improvement in patient-centered outcomes for these patients treated at larger stroke treatment centers as compared to community hospitals is lacking.Methods / design“Efficient Resource Ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…На сегодняшний день недостаточно доказательств, которые могли бы установить критерии для перевода пациентов с ВМК на следующий этап оказания медицинской помощи. Текущие рекомендации предусматривают чрезвычайно широкие и неточные параметры [9]. Необходимы дальнейшие рандомизированные клинические исследования с применением телемедицинских технологий для уточнения показаний для перевода больных с ВМК в медицинские организации следующего уровня.…”
Section: обсуж дениеunclassified
“…На сегодняшний день недостаточно доказательств, которые могли бы установить критерии для перевода пациентов с ВМК на следующий этап оказания медицинской помощи. Текущие рекомендации предусматривают чрезвычайно широкие и неточные параметры [9]. Необходимы дальнейшие рандомизированные клинические исследования с применением телемедицинских технологий для уточнения показаний для перевода больных с ВМК в медицинские организации следующего уровня.…”
Section: обсуж дениеunclassified
“…Detailed rationale and design of EnRICH has been previously described. 7 Briefly, EnRICH is a prospective, multi-site, state-wide cohort designed to assess the comparativeeffectiveness of ICH management at Comprehensive Stroke Certified (CSC) centers, relative to ICH management at Primary Stroke Certified (PSC) or other/ non-certified hospitals. Enrollment began in September 2016 and is currently ongoing at four major metropolitan hubs in the state of Texas (Houston, Austin, San Antonio, and Dallas).…”
Section: Study Design and Populationmentioning
confidence: 99%
“…However, transfers are costly to the healthcare system, as well as to patients and families that must travel farther from their home to the location of care. While many transfers are likely cost-effective from the societal perspective overall,3 data on the cost-effectiveness of ICH patient transfer are limited and conflicting 4. One study reported large differences in costs for gains in quality-adjusted life years depending on patient scenarios,3 and another failed to demonstrate the cost-effectiveness of transfer for these patients 5.…”
Section: Introductionmentioning
confidence: 99%
“…If safe, identification of patients for whom transfer could be avoided would be satisfying to patients and their families, as well as to payers and the healthcare system as a whole. In order to achieve such efficiency, we must consider how to identify the subset of patients for whom transfer could be avoided—there is currently little evidence to inform this decision 4. Our primary objective was to identify factors associated with resource utilisation among patients admitted for ICH.…”
Section: Introductionmentioning
confidence: 99%